School based multifaceted nutrition intervention decreased obesity in a high school: an intervention study from Turkey - Meseri, Reci; Ergin, İsil; Mermer, Gulengul; Hassoy, Hur; Yoruk, Selda; Catalgol, Seyam (Progress in Nutrition, 2018)
Childhood obesity is ever-increasing, and school-based programmes are an intervention area for tackling obesity. In this interventional study, nutritional knowledge and behavior and obesity status were determined for high school students. After multifaceted nutrition and physical activity interventions, nutritional knowledge and behavior and obesity status were re-evaluated. Of the adolescents, one quarter (25.7%) were overweight. Nutritional knowledge and positive nutritional behaviors significantly improved and mean BMI and overweight prevalence significantly reduced after the interventions. Obesity status of the students must be monitored regularly. The effectiveness of interventions should be determined with advanced research, and effective interventions should be implemented to other schools.